Synergy of Parents and Teachers in Students Learning to Instill Religious and Moral Values in the Pandemic Period - Munastiwi, Erni (Jurnal Pendidikan Agama Islam, 2021)
The relationship of parents and teachers in the education unit has an important role in optimizing students' abilities. But the outbreak of the covid-19 pandemic has an impact on education services. Therefore, this study aims to determine tips on the optimization of teachers and parents in the religious and moral aspects of the children during home learning. This research employed a descriptive qualitative method at RA Ar-Rafif Kalasan Yogyakarta (n=15). The data sources of this study are teachers, principals, and parents. Research data were collected through field observations, interviews with teachers and parents, and documentation in form of photos/videos and captures of conversation between teachers and parents. The data validity is tested by using triangulation techniques. The data analysis is acquired by reducing the data that has been collected, presenting the data, and providing conclusions of the research results. The research result shows that synergy of parents and teachers can optimize children’s development aspects of religion and moral obtained through various programs and activities designed by the educators.